Pelatihan Pembuatan Aneka Pangan Olahan Berbasis Tepung Ganyong dan Bunga Telang di Desa Cikondang : Pelatihan Pembuatan Aneka Pangan Olahan Berbasis Tepung Ganyong dan Bunga Telang di Desa Cikondang - Adhi Susilo; Rina Rismaya; Hari Hariadi; EkoYuliastuti Endah Sulistyawati; Athiefah Fauziyyah; Kartika; Wulan Rahmatunisa; Siti Aisah (Universitas Muhammadiyah Palembang, 2025)
The Cikondang Village community, Hantara District, Kuningan Regency, still relies on the use of natural resources to improve the economy of its people. The forest area in this village produces ganyong tubers (Canna discolor) and butterfly pea flowers (Clitoria ternatea) which have not been optimally utilized. To improve the economy of the Cikondang Village community, a dissemination program was carried out in the form of training in making snack bars, food bars, and brownies made from ganyong flour and butterfly pea flowers. The implementation method includes socialization, training, technology introduction, mentoring, and monitoring and evaluation for the sustainability of activities. The data analysis method used in this community service activity is a one group pretest-posttest design which is analyzed non-parametrically using the Wilcoxon test with a significance level of 0.05 to evaluate the difference between the treatment before and after the training. The training program attended by 19 Cikondang villagers showed a significant increase in knowledge based on a pretest value of 58.23% and a posttest of 90.35%. The results of this training are expected to be implemented to present a more diverse and nutritious menu, both for family consumption and for marketing to consumers. Thus, Cikondang Village can become an economically and socially independent village.